FAKTOR SOSIAL EKONOMI YANG MEMPENGARUHI PENGAMBILAN KEPUTUSAN PETANI DALAM SISTEM PENJUALAN SAYURAN - KOMALA DEWI, RATNA; -, SUDIARTINI (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 1, No. 2 Juli 2001)
This research sought to identify (1) socio-economic factors influencing farmers’ decision in selling fresh vegetables in Candikuning village, Tabanan regency, and (2) comparison between income of farmers utilizing Tebasan system and without Tebasan system. Data was collected by using survey method. The 44 farmers with Tebasan system and 20 farmers without Tebasan system have been chosen as a sample in this research. Time period of the study was in planting season in June 1999 until September 1999. The data was analyzed by using Logit Function. The result of the study were (1) income’s farmers, need cash before harvesting time and price risk influencing farmers’ decision in selling the fresh vegetables, and (2) there was no income differences between both kinds of system.
Keywords: Socio-Economic Factors, Decision Making, Selling Vegetables System, and Tebasan System.